Technology of house lifting for relocation purposes / Nur Syarfa Romli - Nur Syarfa Romli, Nur Syarfa (2018)
Lifting and relocating houses is not only a tradition but now it is a technology that people use for some unavoidable reasons. For example, people relocate their houses because of soil erosion and flood problems. Those who faced this problem not only live in rural areas, but some live in the cities as well. The method used to lift and relocate houses are different for each area. Relocation is also needed because of capital improvment made by the government, to prevent from buying new houses and also to move and rotate houses for aesthetic purposes. Thus, the objectives of this study is to understand the method of lifting and relocating house, to identify problems of the methods used, and to propose a new concept in lifting technology. The methodology used in this research is through desk study by making some critical review based on previous and latest research. From the stated problem, it is concluded that this study requires suggestions on the new concept of lifting and relocating houses technology as it is different for urban and rural areas. It is hoped that the results and findings of this study may be useful in the construction industry.